A Closer Look at the Bad Deal Trial: Beyond Clinical Equipoise - Jansen, Lynn A. (The Hastings Center report, 2005)
Some commentators have recently proposed that “clinical equipoise,” although widely accepted, is not necessary for morally acceptable research on human subjects. If this concept is rejected, however, we may find that trials not in the best medical interests of their subjects—”bad deal trials”—could be justified. To avoid exploiting participants, we must find a way to distribute the risks fairly, even if it means embracing radical changes in the way clinical research is conducted.